Factors Influencing Customer Repurchase Intention and Word-Of-Mouth Behavior in Food and Beverage Chain Stores - Dat Tuan Nguyen; Trang Thi Kieu Ta (Bright Publisher, 2026)
This study investigates how customer experience attributes shape perceived value, satisfaction, repurchase intention, and word-of-mouth behavior in Vietnamese food and beverage chain stores. The study addresses the managerial problem of retaining customers in a competitive food and beverage market and contributes to the literature by clarifying a sequential value-satisfaction-behavior mechanism rather than examining isolated direct effects. Drawing on expectation conformation theory and perceived value theory, the research proposes a framework in which store atmosphere, price, perceived quality, product quality, and service quality influence perceived value; perceived value influences satisfaction; and satisfaction affects repurchase intention and word-of-mouth. A mix-methods design was used. The qualitative stage involved expert review and customer pretesting to refine measurement items and improve contextual relevance, while the quantitative stage used a structured survey of customers who had recently experienced food and beverage chain-store services in Vietnam. The research framework and seven empirical tables report the model, respondent profile, measurement items, reliability and validity indices, discriminant validity, hypothesis testing, mediation effects, and explanatory and predictive capability. After data screening, 432 valid responses were analyzed through reliability assessment, validity testing, mediation analysis, and partial least squares structural equation modeling, results show that all five experiential factors positively influence perceived value. Store atmosphere has the strongest effect among the antecedents (β = 0.313), while price has a smaller but significant effect (β = 0.177), suggesting that customers evaluate price through the overall experience rather than cost alone. Perceived value strongly increases satisfaction (β = 0.552), and satisfaction significantly enhances both repurchase intention (β = 0.400) and word-of-mouth (β = 0.369). The findings imply that chain-store managers should coordinate atmosphere, product consistency, service responsiveness, and value-based pricing as an integrated experience system to strengthen satisfaction, repeat purchase, and customer advocacy.